Determinants of property prices in Singapore. - Zhen, Junjie. (2012)
Singapore’s property prices have exhibited mercurial swings in recent years, owing largely to the tumultuous economic environment brought on by the 2008 Global Financial Crisis (GFC). The expansionary monetary policy employed by developed nations in response to the GFC resulted in a large flow of funds into Asia, fuelling worries of high inflation and asset bubbles forming in the region. This paper aims to identify the determinants of asset inflation in both the private and public property markets in Singapore. In addition, this paper is interested in establishing the extent to which housing prices in Singapore are affected by foreign capital inflows – in the form of increased housing loans, and the exact direction of causality. Quarterly data from 1992 to 2011 was utilised. Adopting a Vector Error Correction model, it was found that for the private property market, the significant variables are gross domestic product (GDP), real housing loans and unemployment rate. Supply of new private properties is not a significant determinant in the model, hence implying that property prices in Singapore are largely demand-determined. The significant variables for the Housing and Development Board (HDB) resale market are GDP, real housing loans and the private property price index. Lastly, the Granger-causality test results indicate that causality runs from bank credit to property prices in both property markets, though there is a feedback effect in the HDB resale market. This strongly highlights the importance of controlling bank credit as a policy instrument in curtailing asset inflation in Singapore.